Pengaruh Sistem Informasi Akuntansi Keuangan Terhadap Siklus Hidup Kinerja Keuangan Perusahaan Manufaktur Di Era Pandemi - Otniel Safkaur (Labkat Press KA FTIK UNIKOM, 2021)
The life cycle of a company's financial performance is a picture of the company's finances in a certain period, both in terms of raising funds and distributing funds, which are usually measured by indicators of capital adequacy, liquidity and profitability. Financial performance is a description of the company's financial condition in a certain period. Financial performance is a description of the financial condition of a certain period in achieving company results or goals. The purpose of financial performance is to determine the life cycle of the company's financial management success, especially liquidity conditions, capital adequacy and profitability achieved in the current year and the previous year as well as to determine the ability to utilize all assets owned to generate profits efficiently. The purpose of the company's financial performance is to determine the company's financial condition, so that rational decisions can be made in making decisions within the company. Financial performance can determine the financial position and success in financial management that can be used in making rational decisions in a company. The population in this study were 193 (one hundred and ninety three) manufacturing sectors listed on the IDX and 579 (five hundred seventy-nine samples. The sampling method was carried out by purposive sampling technique based on certain criteria. Data analysis using multiple linear regression analysis was obtained. in this study with the help of computer technology, namely the SPSS For Windows 26 application program. The results of this study indicate that the financial accounting information system has an effect on the life cycle of the company's financial performance in the Pandemi era.